Long-term results of intraoperative electron beam radiation therapy for nonmetastatic locally advanced pancreatic cancer: Retrospective cohort study, 7-year experience with 247 patients at the National Cancer Center in China. Issue 38 (September 2016) - Chen, Yingtai; Che, Xu; Zhang, Jianwei; Huang, Huang; Zhao, Dongbing; Tian, Yantao; Li, Yexiong; Feng, Qinfu; Zhang, Zhihui; Jiang, Qinglong; Zhang, Shuisheng; Tang, Xiaolong; et al.
Abstract : Abstract: To assess prognostic benefits of intraoperative electron beam radiation therapy (IOERT) in patients with nonmetastatic locally advanced pancreatic cancer (LAPC) and evaluate optimal adjuvant treatment after IOERT. A retrospective cohort study using prospectively collected data was conducted at the Cancer Hospital of the Chinese Academy of Medical Sciences, China National Cancer Center. Two hundred forty-seven consecutive patients with nonmetastatic LAPC who underwent IOERT between January 2008 and May 2015 were identified and included in the study. Overall survival (OS) was calculated from the day of IOERT. Prognostic factors were examined using Cox proportional hazards models. The 1-, 2-, and 3-year actuarial survival rates were 40%, 14%, and 7.2%, respectively, with a median OS of 9.0 months. On multivariate analysis, an IOERT applicator diameter < 6 cm (hazards ratio [HR], 0.67; 95% confidence interval [CI], 0.47–0.97), no intraoperative interstitial sustained-release 5-fluorouracil chemotherapy (HR, 0.46; 95% CI, 0.32–0.66), and receipt of postoperative chemoradiotherapy followed by chemotherapy (HR, 0.11; 95% CI, 0.04–0.25) were significantly associated with improved OS. Pain relief after IOERT was achieved in 111 of the 117 patients, with complete remission in 74 and partial remission in 37. Postoperative complications rate and mortality were 14.0% and 0.4%, respectively. Nonmetastatic LAPC patients with smaller size tumors could achieve positive long-term survival outcomes with a treatment strategy incorporating IOERT and postoperative adjuvant treatment. Chemoradiotherapy followed by chemotherapy might be a recommended adjuvant treatment strategy for well-selected cases. Intraoperative interstitial sustained-release 5-fluorouracil chemotherapy should not be recommended for patients with nonmetastatic LAPC. Abstract : Supplemental Digital Content is available in the text